HADAL-ZONE VERKNÃPFT TRÃGHEITSFUSIONSREAKTOR: UTILIZING HADAL ZONE IN REALIZATION OF AN INERTIAL FUSION REACTOR SYSTEM DESIGN BACHELOR DEGREE OF PHYSICS - Liwang, Frederick
The Inertial Confinement Fusion system Hadal-Zone Verknüpft Trägheitsfusionsreaktor (HVT) proposes in this work suggest a utilization of hadal zone of which possesses a notably large pressure in response to lower the required artificial energy input. Validating the superiority of HVT system over the non-hadal zone one was done by comparing the Lawson ???????? parameter alongside with the related temperature ???? from both systems. The ???????? vs. ???? data obtained later show a similar characteristic of which are not found in formal publications. In aspect of such finding, further variation of initial fuel mass ????! was conducted of which further catches a new finding that suggests an absence of tendency between the values of ???????? and the related ???? to the values of ????! apart from the same characteristic in the first finding. From such consistency, it is stated that the data obtained is valid and moreover supported by the existence of a depression zone whose minimal value of ???????? managed to achieve the ignition threshold. Analysis regarding the depression zone further concludes the superiority of HVT system by having a larger ???????? on a smaller ????. Furthermore, such achievement could be extended by suggesting a system capable of operating in room temperature. Such cold fusion system was tested by applying a set of extreme values of ????! and energy input of the system ????" of which further analysis suggest that the validity of such system is yet to be discovered and also suggest a proposal of a new physical parameters.